2021
DOI: 10.3390/children8070558
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination Needs of Families of Children with Down Syndrome: A Scoping Review to Inform Development of mHealth Applications for Families

Abstract: Care coordination is a critical component of health management aimed at linking care providers and health-information-involved care management. Our intent in this scoping review was to identify care coordination needs of families of children with Down syndrome (DS) and the strategies they used to meet those needs, with the goal of contributing to the evidence base for developing interventions by using an mHealth application (mHealth apps) for these families. Using established guidelines for scoping reviews, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
(475 reference statements)
0
4
0
Order By: Relevance
“…In a recent scoping review of care coordination needs of families of children with Down syndrome, Skelton and colleagues [ 24 ] identified three needs: communication, information and utilisation of health resources. Additional needs focused on individual, family and healthcare contextual factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent scoping review of care coordination needs of families of children with Down syndrome, Skelton and colleagues [ 24 ] identified three needs: communication, information and utilisation of health resources. Additional needs focused on individual, family and healthcare contextual factors.…”
Section: Discussionmentioning
confidence: 99%
“…Regular review meetings were held between the two reviewers to discuss and reach a final consensus on any differences of opinion which arose in relation to the inclusion or exclusion of papers. This approach has been applied in other scoping reviews [ 32 ]. Full-text articles of the included papers were then retrieved and screened, using the same approach.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Currently, the mHealth application has been widely used as an educational tool to improve the health and well-being of children, health monitoring, lifestyle, and health promotion (Ruchala & James, 1997). Several previous studies have shown the effectiveness of applications for early detection of hearing loss in children (Yousuf Hussein, Swanepoel, Mahomed, & Biagio de Jager, 2018), education to families with Down Syndrome children (Skelton, Knafl, Van Riper, Fleming, & Swallow, 2021), maternal and child health (Rajak & Shaw, 2019), and tracking the dietary intake (Rajak & Shaw, 2019). The use of monitoring applications to monitor health has been recommended by the World Health Organization (World Health Organization, 2018).…”
Section: Introductionmentioning
confidence: 99%